O biodireito na interface entre ciência e ficção: um estudo do imaginário social a partir da análise do filme Mar adentro - Antedomenico, Edilson [UNESP] (2014)
The study proposed here turned to the study of exploitation cinema to expand the knowledge needed for bioethical reflection. Based on the law (biolaw), the central aim of the research was to understand, through the analysis of the film Mar Adentro, the extent to which cinema can contribute to understanding the social imaginary of assisted death, subject dear to bioethics. The text is structured in two parts: the first deals with theoretical issues, such as brief historical background of bioethics; the biolaw being a split in the field of bioethics and the need for bioethics education for elucidation of the choices involve values related to bioethics. In the second part, undertakes up a reading of said film from three methodological perspectives that characterize the social imaginary of assisted dying: 1) Family/Religious; 2) Legal and 3) Existential. The study showed the wealth of cinema as proposed reflections on bioethical issues in education